The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/635615
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precise tuning of cortical contractility regulates cell shape during cytokinesis

Abstract: ABSTRACTThe mechanical properties of the cellular cortex regulate shape changes during cell division, cell migration and tissue morphogenesis. During cell division, contractile force generated by the molecular motor myosin II (MII) at the equatorial cortex drives cleavage furrow ingression. Cleavage furrow ingression in turn increases stresses at the polar cortex, where contractility must be regulated to maintain cell shape during cytokinesis. How polar cortex contractility con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…However, there could also be molecular contexts in which the redundancy between paralogs is not enough and the unique properties of NMII-A are crucial. These properties are determined mostly by the dynamic properties of the head (the higher ATPase activity, lower duty ratio than the other paralogs) [ 109 ] but also by the tail, that determine cellular localization and filament stability [ 19 , 110 , 111 ].…”
Section: Three Hypotheses To Explain the Correlation Between Genotmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there could also be molecular contexts in which the redundancy between paralogs is not enough and the unique properties of NMII-A are crucial. These properties are determined mostly by the dynamic properties of the head (the higher ATPase activity, lower duty ratio than the other paralogs) [ 109 ] but also by the tail, that determine cellular localization and filament stability [ 19 , 110 , 111 ].…”
Section: Three Hypotheses To Explain the Correlation Between Genotmentioning
confidence: 99%
“…A similar case is that of the formation of the cytokinesis ring. A recent study from the Burnette group has shown that NMII-A/B chimeras are directed to the cytokinesis ring through their tail domains, but the head domain swap decreases separation efficiency [ 111 ], lending support to the argument that full activation of one specific paralog may be required for some functions. In other instances, other fully competent myosin paralogs may compensate for this, if present.…”
Section: Why Do Myh9-rd Patients Display Few But Giant Plateletsmentioning
confidence: 99%
“…In general, epithelial monolayers undergo a variety of characteristic changes in morphology that involve dynamic physical feedback between cells. Previous studies indicated that cortical tension is related to myosin IIA activity ( 60 ). Those motility processes need to be controlled by mechanosensitive signals in order for the proper shape to be reached.…”
Section: Discussionmentioning
confidence: 99%
“…The static tension chain, for which v S = 0, gives the active Young-Laplace law, with the following consequences: (1) the tension chain is straight (H = 0) if the active pressure jump p a counter-balances the (passive) elastic pressure jump p e (i.e., p e + p a = 0); (2) in the absence of a passive pressure jump (i.e., p e = 0), active pressure jump gives rise to a curved tension chain (H = − p a /γ); and (3) tension γ along the chain is constant.…”
Section: Mechanics Of Tension Chainsmentioning
confidence: 99%
“…The distribution of forces across the scale of the cell is dynamically templated by the active cytoskeleton, in particular the cell spanning assemblies of a variety of myosins together with actin filaments and their crosslinkers [1]. Cytoskeletal organisation and remodelling give the cell its dynamical shape and form [2], as well as its adaptive mechanical response [3,4]. In addition, it sets up a global scaffold for the patterning of mesoscale condensates [5] and the relative positioning of subcellular organelles [6], such as the centrosome position [7] and nuclear localization [8,9].…”
Section: Introductionmentioning
confidence: 99%